2008
DOI: 10.1128/aac.00272-08
|View full text |Cite
|
Sign up to set email alerts
|

Species Distribution and In Vitro Antifungal Susceptibility Patterns of 75 Clinical Isolates of Fusarium spp. from Northern Italy

Abstract: Fusarium isolates from 75 Italian patients were identified by molecular methods, and their susceptibilities to antifungals were tested in vitro. Fusarium verticillioides was the species most frequently isolated from deep-seated infections, and F. solani was the species most frequently isolated from superficial infections. F. solani isolates showed high azole MICs, while F. verticillioides isolates showed low posaconazole MICs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
62
2
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 14 publications
10
62
2
1
Order By: Relevance
“…(3,19). As in our study, others have reported the FSSC to be the most resistant members of the genus (37). Finally, studies are needed to evaluate whether and to what extent species-and strain-specific differences in antifungal susceptibility exist within Fusarium.…”
Section: Vol 49 2011 Seven-locus Sequence Analysis Of Fusarium 1895supporting
confidence: 55%
“…(3,19). As in our study, others have reported the FSSC to be the most resistant members of the genus (37). Finally, studies are needed to evaluate whether and to what extent species-and strain-specific differences in antifungal susceptibility exist within Fusarium.…”
Section: Vol 49 2011 Seven-locus Sequence Analysis Of Fusarium 1895supporting
confidence: 55%
“…To this regard, as reviewed by Jain et al (2011), up to now 15 species of Fusarium have been reported as etiological agents of infection, always originated from animal or plant source in nature. In Italy, the number of disseminated infections has greatly increased and F. oxysporum and F. verticillioides, species detected in our survey, result among the most prevalent species involved in human mycoses (Tortorano et al 2008).…”
Section: Discussionmentioning
confidence: 73%
“…Most of the species have shown in vitro resistance to azoles, polyenes, and echinocandins; numerous experimental studies in animals carried out to evaluate different antifungal treatments have had disappointing results, and a favorable outcome was found in less than 50% of the cases (5,7,9,14,15,19).…”
mentioning
confidence: 99%